Sleep Hygiene: A key to improved well-being - Khalid, Wania (Journal of the Pakistan Medical Association, 2026)
Dear Editor, A major problem the modern-day generation facesis a lack of proper sleep. Sleep is a physiological process that repairs the human body. All the wear and tear sustained throughout the day is restoredduring sleep. Proper sleep is essential for the repair of human body functions [1]. Proper sleep hygiene is necessary for a person to attain maximum benefit from this restorative period. Effective sleep can significantly reduce the risk of neurological and cardiovascular diseases. Sleep is also critical for memory formation, consolidation and cognitive function improvement [2]. Understanding sleep hygiene is important for all individuals so they can improve the quality of their sleep. Numerous environmental and lifestyle habits can contribute to better sleep, which is referred to as sleep hygiene. This often encompassessleep patterns, naps, drugs (such as alcohol, nicotine, and caffeine), activities before bed, the bedroom setting, nutrition, and exercise [3]. Physical activity and maintaining a proper diet are essential for both quality daytime activities and sleep. One vital thing is that one should consume the last meal of the day at least a few hours before bedtime. Individuals with late meal times have a poor quality of sleep, as observed in a recent study [4]. Sleep is indeed a vital component of holistic health, the importance of which cannot be overstated. Sleep reduces the progression of various diseases, as sleep and the immune system are closely interlinked [5]. Proper sleep can prevent disease development and delay ageing by making the repair process efficient. There is little awareness among people regarding the proper sleep practices. Physicians should always guide their patients regarding sleep hygiene practices so the quality of life of patients can be improved.